Pendampingan Penulisan Karya Ilmiah bagi Mahasiswa sebagai Upaya Menumbuhkan Kesadaran Literasi di Era Artificial Intelligence - Miftakhul Huda; Hasbi Ash Shiddiqi; Awaliya Safithri (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This community service activity aims to improve students' ability to write scientific papers systematically and critically, as well as foster literacy awareness in the era of Artificial Intelligence (AI) which is full of technological conveniences. Today's students tend to take advantage of technology instantly without understanding the correct academic rules. Therefore, this mentoring is designed to equip students with basic understanding and skills in writing scientific papers that are in accordance with academic standards. The method used in this activity is participatory training through lectures, discussions, and hands-on practice. The activity was carried out in several sessions, starting from the introduction of academic literacy, the structure of scientific papers, to the practice of writing and revising writing. The results of this activity showed that participants experienced an increased understanding of the structure of scientific writing and were more confident in compiling scientific papers independently. In addition, students are also becoming more critical in using AI-based technologies, such as ChatGPT, ethically and responsibly in the writing process. The suggestion from this activity is the need for the sustainability of mentoring programs with a more intensive mentoring model, as well as the integration of academic literacy in the higher education curriculum so that students not only master technology, but also have critical thinking and strong literacy skills.